The Effect of Artificial Intelligence (AI)-Based Learning Media and Student Creativity on Learning Outcomes in the Economics Education Evaluation Course - Ayu Nurul Amalia (Smart Society, 2026)
The use of Artificial Intelligence (AI) in education has grown rapidly due to its potential to support more adaptive learning experiences. However, its effectiveness in improving students’ learning outcomes still requires further investigation, particularly when associated with students’ creativity. This study aims to analyze the effects of AI-based learning media and creativity on learning outcomes in the Economic Learning Evaluation course. The study employed a quantitative method with a quasi-experimental approach using a 2×2 factorial design. The population consisted of 90 fifth-semester students in the Economic Education Study Program, with a sample of 60 students selected through cluster random sampling. Data were collected using creativity instruments and learning outcome tests that met validity and reliability requirements. Data analysis was conducted using two-way ANOVA to examine the main effects and interaction effects among the variables. The results indicate that AI-based learning media do not have a significant effect on learning outcomes, whereas creativity has a positive effect. Furthermore, a significant interaction effect was found between learning media and creativity on learning outcomes. These findings suggest that the effectiveness of AI utilization in learning depends on students’ creativity as a supporting internal factor. This study contributes to the development of AI-based learning models integrated with student creativity and provides implications for the ethical use of AI without neglecting cognitive development and critical thinking skills.